Lithium battery solid electrolyte and production process thereof
By using a composite solid electrolyte of homemade hybrid highly conductive cellulose modified polypyrrole blended polyvinylidene fluoride in lithium batteries, combined with fluorine-doped graphene oxide quantum dots, the problem of conduction blocked by lithium battery solid electrolyte at room temperature is solved, high conductivity and stability are achieved, and the application performance of lithium batteries is improved.
Patent Information
- Application Number
- CN202411640500.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-21
AI Technical Summary
The solid electrolytes of existing lithium batteries are hindered from ion conduction at room temperature, resulting in low ionic conductivity and difficult to meet the practical application needs.
The composite solid electrolyte is prepared by homemade hybrid highly conductive cellulose modified polypyrrole blended polyvinylidene fluoride. The electrolyte conductivity and stability are improved by grafting reaction of carboxymethyl nanocellulose and aminosilane, combined with fluorine-doped graphene oxide quantum dots.
A composite solid electrolyte with high ionic conductivity and high stability is achieved, solving the problem of hindered conduction of existing electrolytes at room temperature, and improving the practical application performance of lithium batteries.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state lithium batteries, and in particular to a lithium battery solid-state electrolyte and a production process thereof. Background Art
[0002] Compared with traditional lead-acid batteries and nickel-metal hydride batteries, lithium-ion batteries have the advantages of high energy density, good cycle performance, and no memory effect, so they are widely used and studied. The commonly used lithium-ion batteries currently use liquid electrolytes containing lithium salts and organic solvents as the medium for transmitting lithium ions. Since organic solvents are volatile and have low melting points, batteries are prone to leakage, flatulence and other undesirable phenomena during use, which makes the battery have safety hazards such as fire and combustion. Therefore, improving the safety performance of batteries has become an urgent requirement. Solid-state lithium batteries use solid electrolytes to replace existing organic liquid electrolytes, so there will be no leakage, flatulence and other undesirable phenomena, which improves the safety performance of batteries and becomes the new darling in the battery field.
[0003] Solid polymer electrolytes are composed only of lithium salts and polymers. Since most polymer matrices have varying degrees of crystallization behavior at room temperature, ion conduction is hindered, and low ionic conductivity makes it difficult to meet the actual application requirements of solid-state batteries. Gel polymer electrolytes are formed by a composite of polymer networks and liquid electrolytes, but the solvents in gel polymer electrolytes can greatly deteriorate the electrode surface chemistry and produce a large number of side reactions. Composite polymer electrolytes are formed by adding inorganic fillers to solid polymer electrolytes. Inorganic fillers are used to reduce the crystallinity of the polymer, thereby improving ionic conductivity and mechanical strength. However, the poor two-phase compatibility and filler agglomeration of composite polymer electrolytes make it difficult for their ionic conductivity to meet actual needs. Summary of the invention
[0004] The purpose of the present invention is to provide a lithium battery solid electrolyte and a production process thereof to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a solid electrolyte for lithium batteries, wherein the solid electrolyte is prepared from a self-made hybrid high-conductive cellulose-modified polypyrrole blended with polyvinylidene fluoride.
[0006] Furthermore, the self-made hybrid highly conductive cellulose is formed by hybridizing highly conductive cellulose with fluorine-doped graphene oxide quantum dots.
[0007] Furthermore, the highly conductive cellulose is prepared by grafting carboxymethyl nanocellulose with aminosilane and clofoate.
[0008] Furthermore, a production process of a lithium battery solid electrolyte comprises the following preparation steps: (1) 0.1 mol of N-aminoethyl-γ-aminopropyltrimethoxysilane was added to 95% ethanol aqueous solution to obtain a mixed solution with a mass concentration of 10%, the solution system was adjusted to a pH of 3.5 with acetic acid, and the N-aminoethyl-γ-aminopropyltrimethoxysilane was hydrolyzed at a speed of 150-250 rpm at room temperature for 1-3 hours to obtain an N-aminoethyl-γ-aminopropyltrimethoxysilane solution; carboxymethyl nanocellulose was added to N-aminoethyl-γ-aminopropyltrimethoxysilane. The silane solution is stirred at 150-250 rpm for 1-3 hours at room temperature to obtain a silane grafted cellulose solution; then clofonate is added to the silane grafted cellulose solution, the temperature is raised to 40-60°C, the solution is stirred at 350 rpm for 1-3 hours, and then the solution is allowed to stand for 12 hours. After the standing period, the solution is centrifuged at a speed of 10000 rpm for 20 minutes, the solid is washed with deionized water for 3 times, and then dried at a vacuum of 0.085 MPa for 2 hours to obtain a highly conductive cellulose; (2) Conductive carbon black and concentrated nitric acid are mixed in a mass ratio of 0.01-0.03:1 and placed in a round-bottom flask, a magnet is placed in the round-bottom flask, the speed of the magnet is adjusted to 10-30r / s, the temperature is set to 130-140°C, and the working time is 24h; after the reaction is completed, the mixed solid is cooled at room temperature to obtain a mixed solid; the mixed solid is mixed with deionized water in a mass ratio of 0.01:1, and then subjected to rotary evaporation treatment in a water bath at 80°C for 12h to obtain a deacidified solid; the deacidified solid is mixed with deionized water in a mass ratio of 1:10 and placed in a quartz boat, argon is introduced into the quartz tube as a driving gas at a temperature of 180°C and a heating time of 3h; after the reaction is completed, the obtained solid is mixed with deionized water in a mass ratio of 1:24, ultrasonically treated at a power of 30kHz for 10-20min, and then centrifuged at a speed of 12000rpm for 30 min; take the upper dispersion, mix it with deionized water at a mass ratio of 1:50, then use a 220nm filter membrane to filter, and then use a 25nm filter membrane to filter again; the solution obtained by filtration is subjected to rotary evaporation treatment in a water bath at 80°C for 12 hours; the solid after rotary evaporation is mixed with deionized water at a mass ratio of 1:30, and then freeze-dried at -40°C for 6 hours to obtain graphene oxide quantum dots; the graphene oxide quantum dots and xenon difluoride are mixed at a mass ratio of 1:5-25, and they are transferred to a quartz boat, two valves are opened, and the air in the quartz tube is exhausted by argon gas, and the valve is closed after the air in the tube is exhausted, and the high-pressure mercury lamp switch is turned on to allow ultraviolet light to shine on the sample in the quartz boat, and the mercury lamp switch is turned off after 10-50 minutes of illumination, and the fluorine-doped graphene oxide quantum dots can be obtained after the quartz tube is naturally cooled; (3) Highly conductive cellulose, deionized water, and fluorine-doped graphene oxide quantum dots were mixed in a mass ratio of 1:30:0.5-2, stirred at 300 rpm for 20 min, and then ultrasonicated at 40 kHz for 30 min, filtered, and dried at 50 ° C for 3 h to obtain hybrid highly conductive cellulose; pyrrole and deionized water were mixed in a mass ratio of 1:10, and then hybrid highly conductive cellulose was added, and the reaction was stirred while ultrasonicating for 20 min, the ultrasonic power was 40 kHz, and the stirring speed was 150 rpm; the mixed solution was heated to 80 ° C for 2 h to self-polymerize and prepare modified polypyrrole; 10 parts of polyvinylidene fluoride, 16-30 parts of modified polypyrrole, 3 parts of dimethyl sulfoxide and 1 part of lithium tetrafluoroborate were mixed, stirred at 120 rpm for 20 min, cast onto a clean glass plate, and coated to form a film, and vacuum dried at an air pressure of 0.085 MPa and a temperature of 60 ° C for 1 h to prepare a composite solid electrolyte membrane.
[0009] Furthermore, in the step (1), the mass ratio of N-aminoethyl-γ-aminopropyltrimethoxysilane, carboxymethyl nanocellulose and clodinafop-butyl is 1-3:1:0.5-2.
[0010] Furthermore, the mass fraction of concentrated nitric acid in step (2) is 65-70%.
[0011] Furthermore, in step (2), the argon gas flow rate is 100 ml / min.
[0012] Furthermore, in step (2), the power of the illuminating mercury lamp is 80-120 W / cm.
[0013] Furthermore, in step (3), the mass ratio of pyrrole to hybrid high conductive cellulose is 5-15:1.
[0014] Furthermore, in step (3), the thickness of the electrolyte membrane is 100-200 μm.
[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: The present invention prepares highly conductive cellulose, attaches fluorine-doped graphene oxide quantum dots for hybridization, and prepares a composite solid electrolyte by blending modified polypyrrole with polyvinylidene fluoride to achieve the effects of high ionic conductivity and high stability.
[0016] Firstly, carboxymethyl nanocellulose is used to undergo a condensation reaction with the silanol group at one end of aminosilane and then grafted onto the nanocellulose. This is beneficial to the dispersion of cellulose and the amino group at the other end of aminosilane is stably combined with the terminal acetylene group of oxalate through an addition reaction. The strong coordination between the oxalate group and Li+ effectively improves the ionic conductivity of carboxymethyl cellulose and produces highly conductive cellulose. Graphene oxide quantum dots are doped with fluoride ions. The rich functional groups on the surface of graphene oxide quantum dots can not only adsorb Li+ and co-deposit with it to inhibit the formation of dendrites, but also adsorb on the surface of metallic lithium to inhibit the shuttle effect, which can ensure the high-rate discharge performance of the battery, effectively improve the transmission capacity of Li+ at the interface, reduce local Li+ aggregation and lithium deposition current, and improve the stability of the electrolyte. Fluorine-doped graphene oxide quantum dots are combined with highly conductive cellulose through functional groups to solve their agglomeration problem. Secondly, the nitrogen-containing functional groups of the pyrrole monomer are used to cross-link pyrrole and hybrid highly conductive cellulose. After in-situ polymerization of pyrrole, the hybrid highly conductive cellulose and pyrrole are interlaced to form a three-dimensional nano-network structure. The polymerized pyrrole provides more connection points for the connection of cellulose, thereby improving the stability of the electrolyte. Polypyrrole is then blended with polyvinylidene fluoride. Polyvinylidene fluoride provides excellent chemical stability and mechanical properties. The modified polypyrrole has high ionic conductivity. The strong hydrogen bonding force between polyvinylidene fluoride and nitrogen-containing functional groups of polypyrrole and hybrid highly conductive cellulose is used to prepare a composite solid electrolyte membrane, which has the advantages of both, making the electrolyte membrane both stable and highly conductive. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0018] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of a lithium battery solid electrolyte prepared in the following examples are as follows: Ionic conductivity: obtained by electrochemical impedance spectroscopy. The prepared polymer membrane was sandwiched between stainless steel sheets (SS) with a diameter of d=14 mm, and assembled into SS / SPE / SS blocking cells in a glove box. The bulk resistance of the battery was measured by the AC impedance method. The test conditions were: frequency of 0.1Hz-100kHz, AC amplitude of 5mV, and open circuit voltage as the initial voltage to measure the bulk resistance Rb. In this test, the temperature was 30°C. The conductivity was then calculated according to the following formula: σ=d / (Rb×S); where σ—lithium ion conductivity (S / cm); d—electrolyte thickness (cm); Rb—electrolyte bulk resistance (Ω); S—stainless steel electrode area (cm 2 ).
[0019] Stability: The samples of the embodiment and the comparative example were stored at room temperature and pressure for 60 days, and then the ion conductivity was tested to calculate the ion conductivity retention rate. Example 1
[0020] (1) 0.1 mol of N-aminoethyl-γ-aminopropyltrimethoxysilane was added to 95% ethanol aqueous solution to obtain a mixed solution with a mass concentration of 10%, and the solution system was adjusted to a pH of 3.5 with acetic acid. The solution was stirred at 150 rpm at room temperature for 1 h to hydrolyze the N-aminoethyl-γ-aminopropyltrimethoxysilane to obtain an N-aminoethyl-γ-aminopropyltrimethoxysilane solution. Carboxymethyl nanocellulose was added to the N-aminoethyl-γ-aminopropyltrimethoxysilane solution, and the solution was stirred at 150 rpm at room temperature. Stir for 1 hour to obtain a silane-grafted cellulose solution; then add clodinafop-butyl to the silane-grafted cellulose solution, heat to 40°C, stir at 350 rpm for 1 hour, and then let stand for 12 hours. After standing, centrifuge at a speed of 10000 rpm for 20 minutes. Take the solid and wash it with deionized water for 3 times, and then dry it at 0.085 MPa in vacuum for 2 hours to obtain high conductive cellulose. The mass ratio of N-aminoethyl-γ-aminopropyltrimethoxysilane, carboxymethyl nanocellulose and clodinafop-butyl is 1:1:0.5. (2) Mix conductive carbon black and concentrated nitric acid with a mass fraction of 65% in a mass ratio of 0.01:1 and place them in a round-bottom flask, put a magnet into the round-bottom flask, adjust the speed of the magnet to 10r / s, set the temperature to 130℃, and work for 24h; after the reaction is completed, cool at room temperature to obtain a mixed solid; mix the mixed solid with deionized water in a mass ratio of 0.01:1, and then perform rotary evaporation in a water bath at 80℃ for 12h to obtain a deacidified solid; mix the deacidified solid with deionized water in a mass ratio of 1:10 and place them in a quartz boat, introduce argon as a driving gas into the quartz tube at a temperature of 180℃ and a heating time of 3h; after the reaction is completed, mix the obtained solid with deionized water in a mass ratio of 1:24, ultrasonically treat at a power of 30kHz for 10min, and then centrifuge at a speed of 12000rpm for 30min; take the upper dispersion and mix with deionized water The obtained solution was subjected to rotary evaporation in a water bath at 80°C for 12 hours; the solid after rotary evaporation was mixed with deionized water at a mass ratio of 1:30, and then freeze-dried at -40°C for 6 hours to obtain graphene oxide quantum dots; the graphene oxide quantum dots were mixed with xenon difluoride at a mass ratio of 1:5, and transferred to a quartz boat, two valves were opened, and the air in the quartz tube was exhausted through argon gas with a flow rate of 100 ml / min, and the valve was closed after the air in the tube was exhausted, and the high-pressure mercury lamp switch was turned on to allow ultraviolet light to shine on the sample in the quartz boat. After 10 minutes of illumination, the mercury lamp switch was turned off, and the power of the irradiation mercury lamp was 80 W / cm, and fluorine-doped graphene oxide quantum dots were obtained after the quartz tube was naturally cooled; (3) Highly conductive cellulose, deionized water, and fluorine-doped graphene oxide quantum dots were mixed in a mass ratio of 1:30:0.5, stirred at 300 rpm for 20 min, and then ultrasonicated at 40 kHz for 30 min. The filtrate was filtered and dried at 50 °C for 3 h to obtain hybrid highly conductive cellulose. Pyrrole and deionized water were mixed in a mass ratio of 1:10, and then hybrid highly conductive cellulose was added. The mass ratio of pyrrole to hybrid highly conductive cellulose was 5:1. The reaction was stirred and ultrasonicated for 20 min. The ultrasonic power was 2.5 W. 40kHz, stirring speed is 150rpm; the mixed solution is heated to 80℃ and reacted for 2h for self-polymerization to prepare modified polypyrrole; 10 parts of polyvinylidene fluoride, 16 parts of modified polypyrrole, 3 parts of dimethyl sulfoxide and 1 part of lithium tetrafluoroborate are mixed, stirred at 120rpm for 20min, poured onto a clean glass plate and scraped to form a film, and vacuum dried at an air pressure of 0.085MPa and a temperature of 60℃ for 1h to prepare a composite solid electrolyte membrane with a thickness of 100μm. Example 2
[0021] (1) 0.1 mol of N-aminoethyl-γ-aminopropyltrimethoxysilane was added to 95% ethanol aqueous solution to obtain a mixed solution with a mass concentration of 10%, the solution system was adjusted to a pH of 3.5 with acetic acid, and the N-aminoethyl-γ-aminopropyltrimethoxysilane was hydrolyzed at 200 rpm at room temperature for 2 h to obtain an N-aminoethyl-γ-aminopropyltrimethoxysilane solution; carboxymethyl nanocellulose was added to the N-aminoethyl-γ-aminopropyltrimethoxysilane solution, and the mixture was stirred at 200 rpm at room temperature for 2 h. Stir for 2 hours to obtain a silane-grafted cellulose solution; then add clodinafop-butyl to the silane-grafted cellulose solution, heat to 50°C, stir at 350 rpm for 2 hours, and then let stand for 12 hours. After standing, centrifuge at a speed of 10000 rpm for 20 minutes. Take the solid and wash it with deionized water for 3 times, and then dry it at 0.085 MPa in vacuum for 2 hours to obtain high conductive cellulose. The mass ratio of N-aminoethyl-γ-aminopropyltrimethoxysilane, carboxymethyl nanocellulose and clodinafop-butyl is 2:1:1.25. (2) Conductive carbon black and concentrated nitric acid with a mass fraction of 68% were mixed in a mass ratio of 0.02:1 and placed in a round-bottom flask. A magnet was placed in the round-bottom flask, the speed of the magnet was adjusted to 20 r / s, the temperature was set to 135°C, and the working time was 24 hours. After the reaction was completed, the mixed solid was cooled at room temperature to obtain a mixed solid. The mixed solid was mixed with deionized water in a mass ratio of 0.01:1, and then subjected to rotary evaporation in a water bath at 80°C for 12 hours to obtain a deacidified solid. The deacidified solid was mixed with deionized water in a mass ratio of 1:10 and placed in a quartz boat. Argon was introduced into the quartz tube as a driving gas at a temperature of 180°C and a heating time of 3 hours. After the reaction was completed, the obtained solid was mixed with deionized water in a mass ratio of 1:24, ultrasonically treated at a power of 30kHz for 15 minutes, and then centrifuged at a speed of 12000rpm for 30 minutes. The upper dispersion was taken and mixed with deionized water. Then mix them in a mass ratio of 1:50, then use a 220nm filter membrane to filter, and then use a 25nm filter membrane to filter again; the solution obtained by filtration is subjected to rotary evaporation in a water bath at 80°C for 12 hours; the solid after rotary evaporation is mixed with deionized water in a mass ratio of 1:30, and then freeze-dried at -40°C for 6 hours to obtain graphene oxide quantum dots; the graphene oxide quantum dots and xenon difluoride are mixed in a mass ratio of 1:15, and they are transferred to a quartz boat, two valves are opened, and the air in the quartz tube is exhausted through argon gas with a flow rate of 100ml / min. After the air in the tube is exhausted, the valve is closed, and the high-pressure mercury lamp switch is turned on to allow ultraviolet light to illuminate the sample in the quartz boat. After 30 minutes of illumination, the mercury lamp switch is turned off. The power of the irradiation mercury lamp is 100W / cm, and fluorine-doped graphene oxide quantum dots can be obtained after the quartz tube is naturally cooled; (3) Highly conductive cellulose, deionized water, and fluorine-doped graphene oxide quantum dots were mixed in a mass ratio of 1:30:1.25, stirred at 300 rpm for 20 min, and then ultrasonicated at 40 kHz for 30 min. The filtrate was filtered and dried at 50 °C for 3 h to obtain hybrid highly conductive cellulose. Pyrrole and deionized water were mixed in a mass ratio of 1:10, and then hybrid highly conductive cellulose was added. The mass ratio of pyrrole to hybrid highly conductive cellulose was 10:1. The mixture was stirred and ultrasonicated for 20 min. The ultrasonic power was 2.5 W. The stirring speed is 40kHz and 150rpm; the mixed solution is heated to 80℃ and reacted for 2h for self-polymerization to prepare modified polypyrrole; 10 parts of polyvinylidene fluoride, 23 parts of modified polypyrrole, 3 parts of dimethyl sulfoxide and 1 part of lithium tetrafluoroborate are mixed, stirred at 120rpm for 20min, poured onto a clean glass plate and scraped to form a film, and vacuum dried at an air pressure of 0.085MPa and a temperature of 60℃ for 1h to prepare a composite solid electrolyte membrane with a thickness of 150μm. Example 3
[0022] (1) 0.1 mol of N-aminoethyl-γ-aminopropyltrimethoxysilane was added to 95% ethanol aqueous solution to obtain a mixed solution with a mass concentration of 10%, and the solution system was adjusted to a pH of 3.5 with acetic acid. The solution was stirred at 250 rpm for 3 h at room temperature to hydrolyze the N-aminoethyl-γ-aminopropyltrimethoxysilane to obtain an N-aminoethyl-γ-aminopropyltrimethoxysilane solution. Carboxymethyl nanocellulose was added to the N-aminoethyl-γ-aminopropyltrimethoxysilane solution and stirred at 250 rpm at room temperature for 3 h. Stir for 3 hours to obtain a silane-grafted cellulose solution; then add clodinafop-butyl to the silane-grafted cellulose solution, heat to 60°C, stir at 350 rpm for 3 hours, and then let stand for 12 hours. After standing, centrifuge at a speed of 10,000 rpm for 20 minutes. Take the solid and wash it with deionized water for 3 times, and then dry it at 0.085 MPa in vacuum for 2 hours to obtain highly conductive cellulose. The mass ratio of N-aminoethyl-γ-aminopropyltrimethoxysilane, carboxymethyl nanocellulose and clodinafop-butyl is 3:1:2. (2) Conductive carbon black and concentrated nitric acid with a mass fraction of 70% were mixed in a mass ratio of 0.03:1 and placed in a round-bottom flask. A magnet was placed in the round-bottom flask, and the rotation speed of the magnet was adjusted to 30 r / s, the temperature was set to 140°C, and the working time was 24 hours. After the reaction was completed, the mixed solid was cooled at room temperature to obtain a mixed solid. The mixed solid was mixed with deionized water in a mass ratio of 0.01:1, and then rotary evaporated in a water bath at 80°C for 12 hours to obtain a deacidified solid. The deacidified solid was mixed with deionized water in a mass ratio of 1:10 and placed in a quartz boat. Argon was introduced into the quartz tube as a driving gas at a temperature of 180°C and the heating time was 3 hours. After the reaction was completed, the obtained solid was mixed with deionized water in a mass ratio of 1:24, ultrasonically treated at a power of 30kHz for 20 minutes, and then centrifuged at a speed of 12000rpm for 30 minutes. The upper dispersion was taken and mixed with deionized water. Then mix them in a mass ratio of 1:50, then use a 220nm filter membrane to filter, and then use a 25nm filter membrane to filter again; the solution obtained by filtration is rotary evaporated in a water bath at 80°C for 12 hours; the solid after rotary evaporation is mixed with deionized water in a mass ratio of 1:30, and then freeze-dried at -40°C for 6 hours to obtain graphene oxide quantum dots; the graphene oxide quantum dots and xenon difluoride are mixed in a mass ratio of 1:25, and they are transferred to a quartz boat, two valves are opened, and the air in the quartz tube is exhausted through argon gas with a flow rate of 100ml / min. After the air in the tube is exhausted, the valve is closed, and the high-pressure mercury lamp switch is turned on to allow ultraviolet light to illuminate the sample in the quartz boat. After 50 minutes of illumination, the mercury lamp switch is turned off. The power of the irradiation mercury lamp is 120W / cm, and fluorine-doped graphene oxide quantum dots can be obtained after the quartz tube is naturally cooled; (3) Highly conductive cellulose, deionized water, and fluorine-doped graphene oxide quantum dots were mixed in a mass ratio of 1:30:2, stirred at 300 rpm for 20 min, and then ultrasonicated at 40 kHz for 30 min. The filtrate was filtered and dried at 50 °C for 3 h to obtain hybrid highly conductive cellulose. Pyrrole and deionized water were mixed in a mass ratio of 1:10, and then hybrid highly conductive cellulose was added. The mass ratio of pyrrole to hybrid highly conductive cellulose was 15:1. The reaction was stirred and ultrasonicated for 20 min. The ultrasonic power was 200 μg / mL. 40kHz, stirring speed is 150rpm; the mixed solution is heated to 80℃ and reacted for 2h for self-polymerization to prepare modified polypyrrole; 10 parts of polyvinylidene fluoride, 30 parts of modified polypyrrole, 3 parts of dimethyl sulfoxide and 1 part of lithium tetrafluoroborate are mixed, stirred at 120rpm for 20min, poured onto a clean glass plate and scraped to form a film, and vacuum dried at an air pressure of 0.085MPa and a temperature of 60℃ for 1h to prepare a composite solid electrolyte membrane with a thickness of 200μm.
[0023] Comparative Example 1 The difference between Comparative Example 1 and Example 2 lies in the difference in step (1), where step (1) is modified to: adding 0.1 mol of N-aminoethyl-γ-aminopropyltrimethoxysilane to 95% ethanol aqueous solution to obtain a mixed solution with a mass concentration of 10%, adjusting the pH of the solution system to 3.5 with acetic acid, and stirring at 200 rpm for 2 h at room temperature to hydrolyze the N-aminoethyl-γ-aminopropyltrimethoxysilane to obtain an N-aminoethyl-γ-aminopropyltrimethoxysilane solution; adding carboxymethyl nanocellulose to the N-aminoethyl-γ-aminopropyltrimethoxysilane solution, and stirring at 200 rpm for 2 h at room temperature to obtain highly conductive cellulose, wherein the mass ratio of N-aminoethyl-γ-aminopropyltrimethoxysilane to carboxymethyl nanocellulose is 2:1; and the remaining steps are the same as those of Example 2.
[0024] Comparative Example 2 The difference between Comparative Example 2 and Example 2 lies in step (1), where step (1) is modified to: add carboxymethyl nanocellulose to 95% ethanol aqueous solution to obtain a mixed solution with a mass concentration of 10%, adjust the solution system to a pH of 3.5 with acetic acid, add clodinafop-butyl to the silane-grafted cellulose solution, heat to 50°C, stir at 350 rpm for 2 h, and then stand for 12 h. After standing, centrifuge at a speed of 10000 rpm for 20 min. Take the solid and wash it 3 times with deionized water, and then dry it at 0.085 MPa in vacuum for 2 h to obtain highly conductive cellulose. The mass ratio of carboxymethyl nanocellulose to clodinafop-butyl is 1:1.25. The remaining steps are the same as those in Example 2.
[0025] Comparative Example 3 The difference between Comparative Example 3 and Example 2 lies in the difference in steps (2) and (3). Steps (2) and (3) are changed to: (2) conductive carbon black and concentrated nitric acid with a mass fraction of 68% are mixed in a mass ratio of 0.02:1 and placed in a round-bottom flask, a magnet is placed in the round-bottom flask, the rotation speed of the magnet is adjusted to 20 r / s, the temperature is set to 135°C, and the working time is 24 hours; after the reaction is completed, the mixed solid is cooled at room temperature to obtain a mixed solid; the mixed solid is mixed with deionized water in a mass ratio of 0.01:1, and then subjected to rotary evaporation treatment in a water bath at 80°C for 12 hours to obtain a deacidified solid; the deacidified solid is mixed with deionized water in a mass ratio of 1:10 and placed in a quartz boat, and argon is introduced into the quartz tube. The temperature of the reaction mixture was 180°C and the heating time was 3 hours. After the reaction, the obtained solid was mixed with deionized water at a mass ratio of 1:24, ultrasonically treated at 30kHz for 15 minutes, and then centrifuged at 12000rpm for 30 minutes. The upper dispersion was taken and mixed with deionized water at a mass ratio of 1:50, and then filtered using a 220nm filter membrane, and then filtered again using a 25nm filter membrane. The solution obtained by filtration was subjected to rotary evaporation in a water bath at 80°C for 12 hours. The solid after rotary evaporation was mixed with deionized water at a mass ratio of 1:30, and then freeze-dried at -40°C for 6 hours to obtain graphene oxide quantum dots. (3) Highly conductive cellulose, deionized water, and graphene oxide quantum dots were mixed in a mass ratio of 1:30:1.25, stirred at 300 rpm for 20 min, and then ultrasonicated at 40 kHz for 30 min. The filtrate was filtered and dried at 50 °C for 3 h to obtain hybrid highly conductive cellulose. Pyrrole and deionized water were mixed in a mass ratio of 1:10, and then hybrid highly conductive cellulose was added. The mass ratio of pyrrole to hybrid highly conductive cellulose was 10:1. The reaction was stirred and ultrasonicated for 20 min. The ultrasonic power was 40 kHz. , stirring speed is 150rpm; the mixed solution is heated to 80℃ and reacted for 2h for self-polymerization to prepare modified polypyrrole; 10 parts of polyvinylidene fluoride, 23 parts of modified polypyrrole, 3 parts of dimethyl sulfoxide and 1 part of lithium tetrafluoroborate are mixed, stirred at 120rpm for 20min, poured onto a clean glass plate and scraped to form a film, and vacuum dried for 1h under the conditions of air pressure of 0.085MPa and temperature of 60℃ to prepare a composite solid electrolyte membrane with a thickness of 150μm; the remaining steps are the same as Example 2.
[0026] Comparative Example 4 The difference between Comparative Example 4 and Example 2 lies in the difference in step (2) (3). Step (2) (3) is changed to: (2) graphene quantum dots and xenon difluoride are mixed in a mass ratio of 1:15, and they are transferred to a quartz boat, two valves are opened, and the air in the quartz tube is exhausted by argon gas at a flow rate of 100 ml / min. After the air in the tube is exhausted, the valve is closed, and the high-pressure mercury lamp switch is turned on to allow ultraviolet light to illuminate the sample in the quartz boat. After irradiation for 30 minutes, the mercury lamp switch is turned off. The power of the irradiation mercury lamp is 100 W / cm. After the quartz tube is naturally cooled, fluorine-doped graphene quantum dots can be obtained; (3) Highly conductive cellulose, deionized water, and fluorine-doped graphene quantum dots were mixed in a mass ratio of 1:30:1.25, stirred at 300 rpm for 20 min, and then ultrasonicated at 40 kHz for 30 min. The filtrate was filtered and dried at 50 °C for 3 h to obtain hybrid highly conductive cellulose. Pyrrole and deionized water were mixed in a mass ratio of 1:10, and then hybrid highly conductive cellulose was added. The mass ratio of pyrrole to hybrid highly conductive cellulose was 10:1. The reaction was stirred and ultrasonicated for 20 min. The ultrasonic power was 40 kHz. , stirring speed is 150rpm; the mixed solution is heated to 80℃ and reacted for 2h for self-polymerization to prepare modified polypyrrole; 10 parts of polyvinylidene fluoride, 23 parts of modified polypyrrole, 3 parts of dimethyl sulfoxide and 1 part of lithium tetrafluoroborate are mixed, stirred at 120rpm for 20min, poured onto a clean glass plate and scraped to form a film, and vacuum dried for 1h under the conditions of air pressure of 0.085MPa and temperature of 60℃ to prepare a composite solid electrolyte membrane with a thickness of 150μm; the remaining steps are the same as Example 2.
[0027] Comparative Example 5 The difference between Comparative Example 5 and Example 2 lies in step (3), whereby step (3) is modified as follows: high conductive cellulose, deionized water and fluorine-doped graphene oxide quantum dots are mixed in a mass ratio of 1:30:1.25, stirred at 300 rpm for 20 min, and then ultrasonicated at 40 kHz for 30 min, filtered and dried at 50° C. for 3 h to obtain hybrid high conductive cellulose; 10 parts of polyvinylidene fluoride, 23 parts of polymethyl methacrylate, 1 part of hybrid high conductive cellulose, 3 parts of dimethyl sulfoxide and 1 part of lithium tetrafluoroborate are mixed, stirred at 120 rpm for 20 min, and then cast onto a clean glass plate and coated by scraping to form a film, and then vacuum dried at an air pressure of 0.085 MPa and a temperature of 60° C. for 1 h to prepare a composite solid electrolyte membrane with a thickness of 150 μm; and the remaining steps are the same as those of Example 2.
[0028] From the comparison of the experimental data of the ionic conductivity of the embodiment and the comparative example, it can be found that the present invention adopts carboxymethyl nanocellulose, and undergoes a condensation reaction with the silanol group at one end of the aminosilane, and is grafted on the nanocellulose, which is beneficial to the dispersion of cellulose, and the amino group at the other end of the aminosilane is stably combined with the terminal alkynyl group of the oxalate through an addition reaction, and the strong coordination between the oxalate group and Li+ effectively improves the ionic conductivity of the carboxymethyl cellulose, and obtains high-conductivity cellulose; fluorine ions are doped with graphene oxide quantum dots, and the rich functional groups on the surface of graphene oxide quantum dots can not only adsorb Li+ and co-deposit with it to inhibit the generation of dendrites, but also can be adsorbed on the surface of metallic lithium to inhibit the shuttle effect, which can ensure the high-rate discharge performance of the battery, effectively improve the transmission capacity of Li+ at the interface, reduce local Li+ aggregation and lithium deposition current, and improve the stability of the electrolyte. Fluorine-doped graphene oxide quantum dots are combined with high-conductivity cellulose through functional groups, which solves its agglomeration problem and improves ionic conductivity. From the comparison of the experimental data of the ion conductivity retention rate of the embodiment and the comparative example, it can be found that the present invention utilizes the nitrogen-containing functional groups of the pyrrole monomer to cross-link the pyrrole and the hybrid high-conductivity cellulose, and then through the in-situ polymerization of the pyrrole, the hybrid high-conductivity cellulose and the pyrrole are interlaced to form a three-dimensional nano-network structure, and the polymerized pyrrole provides more connection points for the connection of the cellulose, thereby improving the stability of the electrolyte; then the polypyrrole is blended with polyvinylidene fluoride, the polyvinylidene fluoride provides excellent chemical stability and mechanical properties, and the modified polypyrrole has high ionic conductivity. The strong hydrogen bonding force between the polyvinylidene fluoride and the nitrogen-containing functional groups of the polypyrrole and the hybrid high-conductivity cellulose is combined to prepare a composite solid electrolyte membrane, which has the advantages of both, so that the electrolyte membrane is both stable and has high conductivity.
[0030] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A solid electrolyte for a lithium battery, characterized in that: The solid electrolyte is prepared from self-made hybrid high-conductive cellulose-modified polypyrrole blended with polyvinylidene fluoride.
2. A lithium battery solid electrolyte according to claim 1, characterized in that: The self-made hybrid high-conductive cellulose is formed by hybridizing high-conductive cellulose with fluorine-doped graphene oxide quantum dots.
3. A lithium battery solid electrolyte according to claim 2, characterized in that: The highly conductive cellulose is prepared from carboxymethyl nanocellulose by grafting clodinafop-butyl with aminosilane.
4. A production process for a lithium battery solid electrolyte, characterized in that: The method comprises the following preparation steps: (1) 0.1 mol of N-aminoethyl-γ-aminopropyltrimethoxysilane was added to 95% ethanol aqueous solution to obtain a mixed solution with a mass concentration of 10%, the solution system was adjusted to a pH of 3.5 with acetic acid, and the N-aminoethyl-γ-aminopropyltrimethoxysilane was hydrolyzed at a speed of 150-250 rpm at room temperature for 1-3 hours to obtain an N-aminoethyl-γ-aminopropyltrimethoxysilane solution; carboxymethyl nanocellulose was added to N-aminoethyl-γ-aminopropyltrimethoxysilane. The silane solution is stirred at 150-250 rpm for 1-3 hours at room temperature to obtain a silane grafted cellulose solution; then clofonate is added to the silane grafted cellulose solution, the temperature is raised to 40-60°C, the solution is stirred at 350 rpm for 1-3 hours, and then the solution is allowed to stand for 12 hours. After the standing period, the solution is centrifuged at a speed of 10000 rpm for 20 minutes, the solid is washed with deionized water for 3 times, and then dried at a vacuum of 0.085 MPa for 2 hours to obtain a highly conductive cellulose; (2) Conductive carbon black and concentrated nitric acid are mixed in a mass ratio of 0.01-0.03:1 and placed in a round-bottom flask, a magnet is placed in the round-bottom flask, the speed of the magnet is adjusted to 10-30r / s, the temperature is set to 130-140°C, and the working time is 24h; after the reaction is completed, the mixed solid is cooled at room temperature to obtain a mixed solid; the mixed solid is mixed with deionized water in a mass ratio of 0.01:1, and then subjected to rotary evaporation treatment in a water bath at 80°C for 12h to obtain a deacidified solid; the deacidified solid is mixed with deionized water in a mass ratio of 1:10 and placed in a quartz boat, argon is introduced into the quartz tube as a driving gas at a temperature of 180°C and a heating time of 3h; after the reaction is completed, the obtained solid is mixed with deionized water in a mass ratio of 1:24, ultrasonically treated at a power of 30kHz for 10-20min, and then centrifuged at a speed of 12000rpm for 30 min; take the upper dispersion, mix it with deionized water at a mass ratio of 1:50, then use a 220nm filter membrane to filter, and then use a 25nm filter membrane to filter again; the solution obtained by filtration is subjected to rotary evaporation treatment in a water bath at 80°C for 12 hours; the solid after rotary evaporation is mixed with deionized water at a mass ratio of 1:30, and then freeze-dried at -40°C for 6 hours to obtain graphene oxide quantum dots; the graphene oxide quantum dots and xenon difluoride are mixed at a mass ratio of 1:5-25, and they are transferred to a quartz boat, two valves are opened, and the air in the quartz tube is exhausted by argon gas, and the valve is closed after the air in the tube is exhausted, and the high-pressure mercury lamp switch is turned on to allow ultraviolet light to shine on the sample in the quartz boat, and the mercury lamp switch is turned off after 10-50 minutes of illumination, and the fluorine-doped graphene oxide quantum dots can be obtained after the quartz tube is naturally cooled; (3) Highly conductive cellulose, deionized water, and fluorine-doped graphene oxide quantum dots were mixed in a mass ratio of 1:30:0.5-2, stirred at 300 rpm for 20 min, and then ultrasonicated at 40 kHz for 30 min, filtered, and dried at 50 ° C for 3 h to obtain hybrid highly conductive cellulose; pyrrole and deionized water were mixed in a mass ratio of 1:10, and then hybrid highly conductive cellulose was added, and the reaction was stirred while ultrasonicating for 20 min, the ultrasonic power was 40 kHz, and the stirring speed was 150 rpm; the mixed solution was heated to 80 ° C for 2 h to self-polymerize and prepare modified polypyrrole; 10 parts of polyvinylidene fluoride, 16-30 parts of modified polypyrrole, 3 parts of dimethyl sulfoxide and 1 part of lithium tetrafluoroborate were mixed, stirred at 120 rpm for 20 min, cast onto a clean glass plate, and coated to form a film, and vacuum dried at an air pressure of 0.085 MPa and a temperature of 60 ° C for 1 h to prepare a composite solid electrolyte membrane.
5. The production process of a lithium battery solid electrolyte according to claim 4, characterized in that: In the step (1), the mass ratio of N-aminoethyl-γ-aminopropyltrimethoxysilane, carboxymethyl nanocellulose and clodinafop-butyl is 1-3:1:0.5-2.
6. The production process of a lithium battery solid electrolyte according to claim 4, characterized in that: The mass fraction of concentrated nitric acid in step (2) is 65-70%.
7. The production process of a lithium battery solid electrolyte according to claim 4, characterized in that: The argon gas flow rate in step (2) is 100 ml / min.
8. The production process of a lithium battery solid electrolyte according to claim 4, characterized in that: The power of the mercury lamp used for illumination in step (2) is 80-120 W / cm.
9. The production process of a lithium battery solid electrolyte according to claim 4, characterized in that: In the step (3), the mass ratio of pyrrole to hybrid high-conductive cellulose is 5-15:
1.
10. The production process of a lithium battery solid electrolyte according to claim 4, characterized in that: The thickness of the electrolyte membrane in step (3) is 100-200 μm.